Social Media Instagram as a Tool to Build a Reputation for Disaster Care (Study on The PT Pertamina Disaster Management CSR Program) - Apriliani, Riski; Nurjanah, Adhianty (Nyimak: Journal of Communication, 2023)
Indonesia is a country with a high level of risk of natural disasters. During 2022, there were 3,531 disaster events which resulted in loss of life, damage to infrastructure, and material and immaterial losses. The high number of disaster cases requires the involvement of stakeholders to participate in disaster management. PT Pertamina is a state-owned company that has a CSR program related to disaster management with a disaster care program. In its implementation, Pertamina carries out disaster management programs as a form of Pertamina’s responsibility in the economic, environmental, and social fields. Pertamina’s Disaster Management CSR program is packaged with the hashtag #PetaminaPeduli which is massively posted on social media Instagram and websites to increase reputation. This study aims to examine how the implementation of the use of new media in an effort to build a reputation for caring for disasters in the Disaster Management CSR Program. The research method used is a case study with a focus on discussing handling the 2022 Cianjur Earthquake disaster, and reviewing Instagram media and websites to increase positive reputation through the hashtag #PertaminaPeduli. Primary data collection techniques were taken from Instagram media and websites, as well as secondary data obtained through document studies, literature studies, and related sources. Data analysis techniques were carried out simultaneously in the data collection process. To test the validity of the data, source triangulation was carried out to obtain accurate and accountable data. The results of this study indicate that Pertamina’s Disaster Management CSR Program consists of basic food assistance, energy assistance for both oil and diesel, as well as assistance for post-disaster trauma healing. An Instagram feature that can publish photos, videos that can be seen by viewers, unlimited captions, as well as like and comment features that will show community engagement in assessing reputation as reflected in the Cianjur 2022 earthquake disaster management CSR program. However, researchers still found a number of comments negative that discusses outside the context of the implementation of CSR programs.Keywords: Social media, reputation, Pertamina, disaster management, Pertamina Peduli ABSTRAKIndonesia merupakan negara dengan tingkat resiko bencana alam yang tinggi. Selama tahun 2022, telah terjadi 3.531 kejadian bencana yang mengakibatkan korban jiwa, kerusakan infrastruktur, serta kerugian materiil dan immateriil. Tingginya kasus bencana memerlukan keterlibatan pemangku kepentingan untuk berpartisipasi dalam penanggulangan bencana. PT Pertamina merupakan perusahaan milik negara yang memiliki program CSR terkait penanggulangan bencana dengan program peduli bencana. Dalam pelaksanaannya, Pertamina menjalankan program penanggulangan bencana sebagai bentuk tanggung jawab Pertamina di bidang ekonomi, lingkungan, dan sosial. Program CSR Penanggulangan Bencana Pertamina dikemas dengan tagar #PetaminaPeduli yang di-posting secara masif di media sosial Instagram dan website untuk meningkatkan reputasi. Penelitian ini bertujuan mengkaji bagaimana implementasi pemanfaatan media baru dalam upaya membangun reputasi peduli bencana dalam Program CSR Penanggulangan Bencana. Metode penelitian yang digunakan adalah studi kasus dengan fokus membahas penanganan bencana Gempa Cianjur 2022, serta meninjau media dan website Instagram untuk meningkatkan reputasi positif melalui tagar #PertaminaPeduli. Teknik pengumpulan data primer diambil dari media dan website Instagram, serta data sekunder diperoleh melalui studi dokumen, studi literatur, dan sumber-sumber terkait. Teknik analisis data dilakukan secara bersamaan dalam proses pengumpulan data. Untuk menguji keabsahan data dilakukan triangulasi sumber untuk mendapatkan data yang akurat dan dapat dipertanggungjawabkan. Hasil penelitian ini menunjukkan bahwa Program CSR Penanggulangan Bencana Pertamina terdiri dari bantuan sembako, bantuan energi baik minyak maupun solar, serta bantuan trauma healing pascabencana. Fitur Instagram yang dapat mempublikasikan foto, video yang dapat dilihat penonton, caption tanpa batas, serta fitur like dan comment yang akan menunjukkan keterlibatan masyarakat dalam menilai reputasi yang tercermin dalam program CSR penanggulangan bencana gempa Cianjur 2022. Namun peneliti masih menemukan sejumlah komentar negatif yang membahas di luar konteks pelaksanaan program CSR.Kata Kunci: Media sosial, reputasi, Pertamina, penanggulangan bencana, Pertamina Peduli